Different strokes for different folks? Comparing pro-environmental intentions between electricity consumers and solar prosumers in Sweden. (November 2020) - Stikvoort, Britt; Bartusch, Cajsa; Juslin, Peter
Abstract: When households invest in photovoltaics, they change from being electricity consumers to solar prosumers, a change that is often implied to also positively affect other pro-environmental behaviours. This article presents a comparison between Swedish consumers and prosumers ( N = 460), concerning (i) whether consumers and prosumers engage in pro-environmental behaviours for different reasons, and (ii) whether prosumers and consumers differ in their intention to engage in these behaviours and if they find the reasons for doing so differentially motivating. Early and late prosumers are moreover compared to see whether time of investment influenced the reasons to engage in pro-environmental behaviours. The data show that both consumers and prosumers engaged in pro-environmental behaviours for the same reasons: convictions that behaviours contribute to the environment and one's life-quality. Moreover, both prosumers and consumers were more inclined to engage in pro-environmental behaviour when they saw less economic gain in those behaviours. Both groups were also motivated by a perceived moral responsibility and by a high self-assessed awareness of one's electricity consumption and saving possibilities. Consumers and prosumers, however, differed in the degree to which they were compelled by these reasons: prosumers had higher confidence that pro-environmental behaviours would benefit the environment, improve their comfort and life-quality, they felt more moral responsibility to perform such behaviours and assessed their electricity awareness as higher. This study confirms and identifies systematic differences between consumers and prosumers in their pro-environmental intentions and motivations, and the differences are discussed in terms of initial self-selection and possible spill-over effects.